Unusual phosphine oxidation: new triazolopyridyl-quinolyl phosphine oxide fluorescent dyes. Issue 38 (26th March 2015) - Ballesteros-Garrido, R.; Abarca, B.; Ballesteros, R.; Colobert, F.; Leroux, F. R.; García-España, E.
Abstract : 3-(2-Pyridyl)-[1, 2, 3]triazolo[1, 5- a ]quinolylphosphines suffer an unusual phosphine oxidation due to their special geometry that allows a σ-donation of the nitrogen (N1) lone pair to phosphorus. Abstract : 3-(2-Pyridyl)-[1, 2, 3]triazolo[1, 5- a ]quinolylphosphines suffer an unusual phosphine oxidation due to their special geometry that allows a σ-donation of the nitrogen (N1) lone pair to phosphorus. This family of compounds behaves as strong fluorophores with high quantum yields.